216k views
1 vote
Solve for the indicated variable. -10=xy + z for x

1 Answer

5 votes

To solve for x, you undo what was done to x. The variable x is ...

  • multiplied by y
  • added to z

You "undo" these operations in the reverse order, so first we undo the addition of z. We accomplish that by adding the opposite of z:

... -10 -z = xy

Now, we undo the multiplication by y. We accomplish that by multipying by the reciprocal of y.

... (-10 -z)/y = x

We can rearrange this, if you like.


x=(-10-z)/(y)

And, if you want, you can factor out the minus sign.


x=-\left((z+10)/(y)\right)

User McLeary
by
5.3k points